The Growth of Doctorates in Germany - Kehm, Barbara (International Higher Education, 2023)
The number of doctoral degrees awarded in Germany, which was already high, is growing. The German Excellence Initiative is the major growth factor. Doctorates awarded by universities of applied sciences (UASs) do not play a statistically significant role (yet). However, the traditional university monopoly on awarding doctoral degrees is clearly eroding. In the face of “massification” of the doctorate, Germany still tends to opt for horizontal diversification rather than vertical stratification.